2018
DOI: 10.1007/s10926-018-9803-9
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Validity of the Work Ability Index Among Employees in Germany

Abstract: Purpose The Work Ability Index (WAI) is a routinely applied instrument for the assessment of work ability. It is a single score index, based on the implicit assumption of a single factor underlying the construct of work ability. The few studies with a focus on the WAI's factor structure are mainly based on non-representative samples. The objective of this study was to examine the factor structure of the WAI within a representative sample of employees working in Germany, applying analysis procedures that consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 23 publications
2
28
0
2
Order By: Relevance
“…Work ability was measured by the second dimension of the validated Work Ability Index [WAI (Hasselhorn and Freude 2007;Tuomi et al 1999)]. Previous validation studies have suggested a two-factorial structure of the WAI with a healthrelated and a subjective work ability factor (Freyer et al 2019;Martus et al 2010). Since using the health-related factor might have introduced a construct overlap to depressive symptoms, the second dimension was used to measure subjective work ability.…”
Section: Methodsmentioning
confidence: 99%
“…Work ability was measured by the second dimension of the validated Work Ability Index [WAI (Hasselhorn and Freude 2007;Tuomi et al 1999)]. Previous validation studies have suggested a two-factorial structure of the WAI with a healthrelated and a subjective work ability factor (Freyer et al 2019;Martus et al 2010). Since using the health-related factor might have introduced a construct overlap to depressive symptoms, the second dimension was used to measure subjective work ability.…”
Section: Methodsmentioning
confidence: 99%
“…Comparisons were also made using the results of studies that did not include nursing/healthcare personnel. The study among German workers confirmed a two-factor structure (Factor-1: subjective WA and resources, Factor-2: health related factor) ( 26 ), while the study among Brazilian electrical company workers confirmed a three-factor structure (Factor-1: mental resources, Factor-2: self-perceived WA, Factor-3: presence of diseases and health-related limitations) ( 18 ). Recently, a three-factor structure was also confirmed among Iranian workers in petrochemical and car manufacturing industries ( 25 ).…”
Section: Discussionmentioning
confidence: 92%
“…WAIQ is a widely used instrument all over the world ( 3 ). Its reliability and validity have been tested in various working populations so far ( 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ), including among nurses, where it proved to be a very predictive instrument ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Martus et al [40] suggested two correlated factors “subjectively estimated work ability“ and “objective health status“ as an adequate WA model. A recent confirmatory factor analysis by Freyer et al [41], employing data from a large sample of German employees aged 31–60 years, supported these findings. The authors recommended not to use the one-dimensional WAI sum-score but to compute two sub-scores instead [42].…”
Section: Introductionmentioning
confidence: 81%
“…As usual, in investigations on construct validation, the relationships of the variables are tested by correlations. Since WAI, WAI 1 and WAI 2 do not to follow a normal distribution [55], [29] and we cannot assume all the indicators to be interval scaled [41], we use the Spearman´s rho (ρ) for ordinal correlation in all analyses. An aspect to be noted is the fact that correlation between WAI 1 and 2, each, with WAI are partial autocorrelations, thus leading to higher coefficients.…”
Section: Methodsmentioning
confidence: 99%